Depth-resolved chemical modification of porous silicon by wavelength-tuned irradiation - Guan, B.; Ciampi, Simone; Luais, E.; James, M.; Reece, P.; Gooding, J. (American Chemical Society, 2012)
The ability to impart discrete surface chemistry to the inside and outside of mesoporous silicon is of great importance for a range of biomedical applications, from selective (bio)sensing to tissue-specific drug delivery. Here we present a generic strategy toward achieving depth-resolved functionalization of the external and internal porous surfaces by a simple change in the wavelength of the light being used to promote surface chemical reactions. UV-assisted hydrosilylation, limited by the penetration depth of UV light, is used to decorate the outside of the mesoporous structure with carboxylic acid molecules, and white light illumination triggers the attachment of dialkyne molecules to the inner porous matrix.